Perkembangan Ekonomi Syariah di Ranting Muhammadiyah Gading - Indri Wulandari; Prastiwi, Iin Emy; Agus Marimin (ITB AAS INDONESIA Surakarta, 2026)
This study aims to describe and analyze the development of Islamic economics at the grassroots level through the case of Ranting Muhammadiyah Gading, a local branch of the Muhammadiyah organization located in a rural communit. Ranting Muhammadiyah Gading exemplifies this shift by initiating and managing various sharia-based economic activities, including the establishment of Islamic cooperatives, the operation of local Baitul Maal wat Tamwil (BMT), development of community-based micro-enterprises, and the facilitation of Islamic entrepreneurship training. This research uses a qualitative descriptive approach with a case study method. Data were collected through in-depth interviews with local leaders and economic actors, field observations, and documentation of economic programs initiated by the ranting. The findings reveal that the development of Islamic economics in Ranting Muhammadiyah Gading is driven by a combination of strong visionary leadership, active community participation, institutional support from Muhammadiyah's charitable arms (such as local mosques and schools), and collaboration with external Islamic financial institutions. These factors contribute significantly to the growth of local sharia-compliant economic institutions that prioritize justice, mutual benefit, and ethical business conduct. The economic programs have not only improved the economic resilience of the local community but have also strengthened social cohesion and religious awareness among its members. However, the development process is not without challenges, including limited capital, inadequate managerial skills, and uneven levels of Islamic financial literacy among members. In conclusion, the case of Ranting Muhammadiyah Gading demonstrates that grassroots Islamic economic initiatives can serve as effective instruments for community-based economic empowerment. The experience of this local Muhammadiyah branch offers valuable insights into how faith-based organizations can play a transformative role in developing a sustainable and ethical economic system. This study recommends the enhancement of institutional capacity, continuous education in Islamic economic principles, and expanded cooperation with regional and national sharia financial institutions to further strengthen the impact of Islamic economic practices at the local level.